The Working Records of Krekenava Photographer Tadas Bajorūnas - Pikelytė, Zita (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English]The article analyzes the records of the photographer Tadas Bajorūnas, who lived and worked in Krekenava town (Panevėžys County) in 1920–1945. These records are written in a simple notebook, which contains the photographer‘s generated revenues of the year 1934–1941. After making a study of the notes, we can see if in that period the photography taking was a profitable business in a small town. Also we could see in what additional activities the photographer was engaged in and what kind of activities were most profitable for him. After the analysis of the notebook records the revenues were divided into three main groups according to the type of activity: the revenue from photographic services (they accounted for an average of 67 per cent of all the income records), the revenue from watch repairing and other revenue (for various jobs, etc.). Data collected from various sources show that not just T. Bajorūnas, but also the other photographers from smaller towns had a few crafts and were engaged in additional businesses. Many of them were skilled experimenters, constructers, repairers, who were able to carry out works, which required large-diligence, patience and precision. Tadas Bajorūnas’ records reveal not only his economic situation, but also a lot of information about the nature of his work, literacy, language usage nuances. It is the unique document and the interesting source of the knowledge of our country’s past events.